Algorithm and theorem on student activity problems - V. Longani (2018)
© 2015 by the Mathematical Association of Thailand. All rights reserved. In this paper, Student Activity Problems are defined. The problems are about joint activities among n≥2 schools. There are p > n different activity rooms and each school provide p students to join the activities. In each day, each student has to join an activity with a condition that in each room there are n students from n different schools. It is required that each student participate all p activities in p days and each has a chance to work only once with every student from other schools. An algorithm is proposed for such arrangement and a related theorem is also given.